ACTUALITY AND DECISION OF PROBLEMS OF TREATMENT KHIMIOREZISTENTNY OF TUBERCULOSIS - Філатова, О.В. (World of Medicine and Biology, 2012)
Results of analysis of accessible literature are about rezistentnist’ of mikobakteriy of tuberculosis to antiphthisic preparations, cases of tuberculosis with plural and extended rezistentnistyu, factors, which promoted development of khimiorezistentnosti, treatment of patients with, khimiorezistentniy tuberculosis, allow to think that yet many not studied tasks and questions are, answers for which would improve a very unfavorable situation with khimiorezistentnim tuberculosis. It is here possible to take the necessity of receipt of reliable information about frequency and spectrum of rezistentnosti of MBT to antiphthisic preparations, state and lacks of organization of exposure of patients with khimiorezistentnim tuberculosis. It is also necessary to pay regard to lacks of organization of their treatment. Generalization of these information will allow to develop the permanent standard of organization of exposure and treatment of patients with khimiorezistentniy tuberculosis, that would be able very substantially to improve control above the epidemic of khimiorezistentnogo tuberculosis.